Impact of Motivation and Job Satisfaction on Performance Employee (Study in Waroeng Spesial Sambal) - Pribadi Widyatmojo, Tia Apriani & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Employees are foundation of company. Company needs high motivationemployee. Job satisfaction is needed for optimal performance. The goal of thisresearch to investigate the impact of motivation toward employee performance,job satisfaction toward employee performance, job satisfaction towardmotivation and performance toward job satisfaction. The benefit of thisresearch is to explain the research gab, that is not every of the job satisfactionand motivation influence performance not significantly.Hopeful this research can be a reference for another reseacher especiallymotivation measurement. This research uses McClelland motivation theory.This research conclude that motivation influence on employee performance, jobsatisfaction influence employee performance, job satisfaction influencemotivation and performance influence job satisfaction significantly.The study used 74 respondents and the overall level of staff respondents wereemployees of Waroeng Spesial Sambal (SS) Yogyakarta. Motivation haspositive effect on Employee Performance. Job satisfaction has positiveinfluence on Employee Performance. Job satisfication has positive influence onmotivation. And Employee performance has positive influence on Jobsatisfaction..Keywords: [ motivation, job satisfaction, employeeâ performance]